The Skilled Helper / A Problem Management Approach to Helping - Egan Gerard (Brooks/Cole Publishing Company, 1998)
Laying the Groundwork, Introduction, Overview of the Helping Model, Stage I of the Helping Model and Advanced Communication Skills, Helping Clients Tell Their Stories, Reluctant and Resistant Clients, The Nature of Challenging - Helping Clients Challenge Themselves, Specific Challenging Skills, The Wisdom of Challenging, Leverage: Helping Clients Work on the Right Things, Helping Clients Determine What They Need and Want, What Do You Need and Want? Possibilities for a Better Future, What Do You Really Want? Moving from Possibilities to Choices, Commitment - What are You Willing to Pay for What You Want?, Helping Clients Work for What They Need and Want, Strategies for Action - What Do I Need to Do to Get What I Need and Want?, Best-Fit Strategies - What Strategies are Best for Me?, Helping Clients Make Plans - What Kind of Plan will Help me Get What I Need and Want?, The Action Arrow: Making It All Happen, Making It All Happen: Helping Clients Get What They Want and Need, Practical Appendices: Further Useful Material, References, Name and Subject Index.